PELATIHAN PENGGUNAAN MICROSOFT OFFICE DAN MEDIA PEMBELAJARAN DARING UNTUK MENUNJANG KEGIATAN BELAJAR MENGAJAR BAGI GURU SD INPRES PERUMNAS 2 WAENA KOTA JAYAPURA - Tulak , Noper; Sari, Wahyu Kumala (JURNAL PENGABDIAN PAPUA, 2023)
Mastery of information technology for teachers is a reflection of the professionalism of their profession. One indicator of a professional teacher can be seen from the ability to adapt to scientific developments in line with advances in Information Technology. In addition to increasing professionalism in their field, mastery of information technology can also help teachers manage class administration to support the teaching and learning process. Make lesson plans, recap student learning outcomes and make teaching materials. In addition, socialization of school activities also needs to involve information technology assistance so that work becomes more efficient. Common problems that often arise related to information technology are constrained by the ability and skills of teachers in using basic Microsoft Office applications. To overcome these problems, the community service team provided training to improve the skills of teachers at SD Inpres Perumans 2 Waena in utilizing Microsoft office applications and online learning media. The training is expected to be able to support teacher professionalism in improving the quality of education. The selection of topics and community service targets is based on factual conditions where there are limited abilities and skills of teachers in using basic applications as part of information technology. Keywords: Microsoft Office; Elementary Teachers; Inpres Perumnas 2 Elementary School